The Role Of Ambidextrous Leadership In Driving Employee Innovation and Competitive Advantage In East Java's UMKM Banks - Muzakki, Muzakki; Herryanto, Asep; Permadi, Edo Galih (Universitas Sains dan Teknologi Komputer, 2024)
The purpose of this study is to explore the relationship between ambidextrous leadership and employee innovation and its impact on competitive adventage. Respondents who participated in this study were 147 respondents who came from employees and branch managers of Bank UMKM East Java. The data collected were processed using SEM PLS version 3.0. The results of this study indicate that ambidextrous leadership has a significant effect on employee innovation. Ambidextrous leadership also has a significant effect on competitive adventage. Employee innovation also has a significant effect on competitive adventage. This study enriches the literature on ambidextrous leadership by emphasizing the importance of this leadership style in encouraging employee innovation and increasing competitive advantage. This strengthens the assumption that leaders who are able to balance exploration and exploitation can provide better results.